Pharmacological Potential and Chemical Characterization of Bridelia ferruginea Benth.-A Native Tropical African Medicinal Plant - Mohamad Fawzi Mahomoodally; Sharmeen Jugreet; Kouadio Ibrahime Sinan; Gokhan Zengin; Gunes Ak; Ramazan Ceylan; József Jekő; Zoltán Cziáky; Paola Angelini; Giancarlo Angeles Flores; Roberto Venanzoni; Simonetta Cristina Di Simone; et al. (MDPI AG, 2021)
To avail the possible pharmacological actions of Brideliaferruginea Benth., the present investigation was designed to quantitatively analyze the total flavonoid and phenolic contents and assess the various antioxidant and enzyme inhibition properties of leaf and stem bark extracts (ethyl acetate, water and methanolic) of B. ferruginea. Anti-proliferative effect was also investigated against human colon cancer cells (HCT116) as well as the antimicrobial potential against multiple bacterial and fungal (yeasts and dermatophytes) strains. The methanolic and water extracts of the stem bark demonstrated the highest phenolic content (193.58 ± 0.98 and 187.84 ± 1.88 mg/g, respectively), while the leaf extracts showed comparatively higher flavonoid contents (24.37-42.31 mg/g). Overall, the methanolic extracts were found to possess the most significant antioxidant potency. Compared to the other extracts, methanolic extracts of the B. ferruginea were revealed to be most potent inhibitors of acetyl- and butyryl-cholinesterases, tyrosinase α-amylase, except α-glucosidase. Only the ethyl acetate extracts were found to inhibit glucosidase. Additionally, the stem bark methanolic extract also showed potent inhibitory activity against E. coli and gram-positive bacteria (MIC (minimum inhibitory concentration): 2.48-62.99 µg/mL), as well as all the tested fungi (MIC: 4.96-62.99 µg/mL). In conclusion, B. ferruginea can be regarded as a promising source of bioactive compounds displaying multifunctional pharmacological activities and thus is a potential candidate for further investigations in the endeavor to develop botanical formulations for pharmaceutical and cosmeceutical industries.